Arctic cisco stomach content data, Prudhoe Bay, August 2009 - Vanessa R von Biela; Christian E Zimmerman; Brian R Cohn; Jeffrey M Welker (USGS Science Data Catalog, 2016)
This data set documents the stomach contents of age-0 Arctic cisco (Coregonus autumnalis) captured in Prudhoe Bay, Alaska in August 2009. The analysis of this data was published in von Biela et al. 2013 (Polar Biology 36:137-146, doi:10.1007/s00300-012-1244-x). The data consists of counts of specific zooplankton taxa from individual fish stomachs.